Soil physical change and sugarcane stalk yield induced by cover crop and soil tillage - Farhate, Camila Viana Vieira [UNESP]; de Souza, Zigomar Menezes; Cherubin, Maurício Roberto; Lovera, Lenon Henrique; de Oliveira, Ingrid Nehmi; Guimarães Júnnyor, Wellingthon da Silva; La Scala Junior, Newton [UNESP] (Revista Brasileira de Ciencia do Solo, 2022)
Conventional tillage and intensive machinery traffic are the major causes of physical soil degradation in sugarcane fields. This study evaluates the impact of adopting conservation management practices during sugarcane planting on soil physical properties and stalk yield of sugarcane in the municipality of Ibitinga, state of São Paulo, Brazil. The experimental design (split-block) included four cover crops and three soil tillage systems, with three repetitions. For comparison purposes, a control treatment was also included (without cover crop and under conventional tillage). Sampling for soil physical analysis was performed in three layers that coincide with soil horizons A (0.00-0.20 m), AB (0.20-0.30 m), and Bt (0.30-0.70 m), during cane-plant and first sugarcane ratoon cycles. The results showed that cultivation of sunn hemp associated with deep subsoiling induced high stalk yield of sugarcane in both production cycles, cane plant (116 Mg ha-1) and first ratoon (114 Mg ha-1), with a net gain of 11 and 9 Mg ha-1 compared with the control treatment, respectively. However, these results were not sufficient to induce significant differences in sugarcane yield. Nonetheless, the use of sunn hemp and millet, associated with subsoiling (at 0.40 or 0.70 m depth) during sugarcane planting, are promising management strategies to sustain better soil’s physical quality when compared to traditional management, conventional soil tillage without cover crops and/or cash crop, as peanuts, that increase the risks of soil compaction and physical degradation.
Keywords: Millet; No-tillage system; Soil compaction; Subsoiling; Sunn hemp